DESA BOJONG MURNI, MERAIH ASA MELALUI HARUMNYA MINYAK ATSIRI - Haris, Helmi; Suarman Sudarsah, Agus; Muliya Puti, Ade; Ratna Ningsih, Sri; Septiani, Bunga; Aulia Rahmah, Widia; Akim, Restu; Hertiani, Euis; Rachmasari, Annisa (LPPM Universitas Islam 45 Bekasi, 2024)
The Sadar Tani Muda Forest Farmer Group is engaged in trigona honey bee cultivation and agriculture, especially seasonal crops in the form of vegetable commodities and essential oil source plants, namely nutmeg, cloves, ginger, and citronella commodities. The problem is the unavailability of essential oil processing technology to process the harvest of residents, how to manage the management of the distillation business and marketing of essential oils. The purpose of the Village Innovation Ambassador Programme is to introduce essential oil distillation technology, provide guidance on farm business management for cultivating and processing essential oils, find marketing links for the essential oils produced, and support the MBKM Campus Merdeka Belajar programme, especially KPI 2 = Students get off-campus experience, KPI 3 = Lecturers have off-campus activities, and KPI 5 = Lecturers' work results are used by the community. The method of implementing community service uses several methods, namely socialisation, counseling, training, coaching and mentoring to the young farmer conscious forest farmer group of Bojong Murni Village, Ciawi-Bogor Regency. The results of community service activities are in the form of increased knowledge and information about essential oil distillation in the Young Farmer Conscious Forest Farmer Group and increased awareness so that they can prepare themselves for the establishment of home industry scale essential oil distillation in the following year.